Intranasal corticosteroid therapy for obstructive sleep apnoea in patients with co-existing rhinitis. Issue 1 (23rd December 2003) - Kiely, J L; Nolan, P; McNicholas, W T
Abstract : Background: Increased nasal airflow resistance (NAR) may contribute to the pathophysiology of obstructive sleep apnoea syndrome (OSAS) but studies investigating the effects of relieving nasal obstruction in OSAS have produced differing results. There are no reports of intranasal corticosteroid therapy in adult OSAS patients with reversible nasal obstruction. Methods: We evaluated an intranasal corticosteroid, fluticasone propionate, in 24 consecutive snorers with associated rhinitis using a randomised, placebo controlled, crossover design. Patients underwent polysomnography, snoring noise, and NAR measurements at baseline and after each 4 week treatment period. Results: Twenty three patients completed the protocol and were divided into an apnoeic group (group A; 13 patients) and a non-apnoeic snoring group (group S; 10 patients) based on an apnoea-hypopnoea frequency (AHI) of ⩾10/h or <10/h. AHI was significantly lower following treatment with fluticasone than with placebo in the total population (median (quartile range) 11.9 (22.6) v 20 (26.3); p<0.05) and in group A (23.3 (21.3) v 30.3 (31.9); p<0.05). Median (95% confidence interval) within subject differences for AHI were −3.2 (−17.7 to −0.2) in the total population and −6.5 (−29.5 to 1.8) in group A. NAR was also lower on fluticasone (2.74 (1.21) v 3.27 (1.38), p<0.01), within subject difference being −0.45 (95% CI −0.87 to −0.21). The changes in AHI and NAR in group A were significantly correlated ( r  = 0.56; p<0.05). Snoring noise and sleep quality were unchanged but daily diary records indicated subjective improvements in nasal congestion and daytime alertness with fluticasone (p<0.02). Conclusions: Intranasal fluticasone is of benefit to some patients with OSAS and rhinitis. The data suggest that this form of nasal obstruction may contribute to the pathophysiology of OSAS.